A Kelch Domain-Containing F-Box Coding Gene Negatively Regulates Flavonoid Accumulation in Muskmelon . Issue 3 (10th September 2015) - Feder, Ari; Burger, Joseph; Gao, Shan; Lewinsohn, Efraim; Katzir, Nurit; Schaffer, Arthur A.; Meir, Ayala; Davidovich-Rikanati, Rachel; Portnoy, Vitaly; Gal-On, Amit; Fei, Zhangjun; Kashi, Yechezkel; et al.
Abstract : Posttranscriptional regulation shifts the metabolic flux of flavonoids toward coumarin and general phenylpropanoids. Abstract: The flavonoids are phenylpropanoid-derived metabolites that are ubiquitous in plants, playing many roles in growth and development. Recently, we observed that fruit rinds of yellow casaba muskmelons ( Cucumis melo 'Inodorous Group') accumulate naringenin chalcone, a yellow flavonoid pigment. With RNA-sequencing analysis of bulked segregants representing the tails of a population segregating for naringenin chalcone accumulation followed by fine mapping and genetic transformation, we identified a Kelch domain-containing F-box protein coding ( CmKFB ) gene that, when expressed, negatively regulates naringenin chalcone accumulation. Additional metabolite analysis indicated that downstream flavonoids are accumulated together with naringenin chalcone, whereas CmKFB expression diverts the biochemical flux toward coumarins and general phenylpropanoids. These results show that CmKFB functions as a posttranscriptional regulator that diverts flavonoid metabolic flux.